mTOR inhibitor improves autistic-like behaviors related to Tsc2 haploinsufficiency but not following developmental status epilepticus - Petrasek, Tomas; Vojtechova, Iveta; Klovrza, Ondrej; Tuckova, Klara; Vejmola, Cestmir; Rak, Jakub; Sulakova, Anna; Kaping, Daniel; Bernhardt, Nadine; de Vries, Petrus J; Otahal, Jakub; Waltereit, Robert (Journal of neurodevelopmental disorders, 2021)
BACKGROUND: Tuberous sclerosis complex (TSC), a multi-system genetic disorder often associated with autism spectrum disorder (ASD), is caused by mutations of TSC1 or TSC2, which lead to constitutive overactivation of mammalian target of rapamycin (mTOR). In several Tsc1+/- and Tsc2+/- animal models, cognitive and social behavior deficits were reversed by mTOR inhibitors. However, phase II studies have not shown amelioration of ASD and cognitive deficits in individuals with TSC during mTOR inhibitor therapy. We asked here if developmental epilepsy, common in the majority of individuals with TSC but absent in most animal models, could explain the discrepancy. METHODS: At postnatal day P12, developmental status epilepticus (DSE) was induced in male Tsc2+/- (Eker) and wild-type rats, establishing four experimental groups including controls. In adult animals (n = 36), the behavior was assessed in the paradigms of social interaction test, elevated plus-maze, light-dark test, Y-maze, and novel object recognition. The testing was carried out before medication (T1), during a 2-week treatment with the mTOR inhibitor everolimus (T2) and after an 8-week washing-out (T3). Electroencephalographic (EEG) activity was recorded in a separate set of animals (n = 18). RESULTS: Both Tsc2+/- mutation and DSE caused social behavior deficits and epileptiform EEG abnormalities (T1). Everolimus led to a persistent improvement of the social deficit induced by Tsc2+/-, while deficits related to DSE did not respond to everolimus (T2, T3). CONCLUSIONS: These findings may contribute to an explanation why ASD symptoms in individuals with TSC, where comorbid early-onset epilepsy is common, were not reliably ameliorated by mTOR inhibitors in clinical studies.
Keywords: TOR Serine-Threonine Kinases; Tuberous Sclerosis Complex 2 Protein; Haploinsufficiency; TOR serin-threoninkinasy; status epilepticus; krysa rodu Rattus; Autism spectrum disorders; zvířata; Tuberous sclerosis complex; autistická porucha; Autistic Disorder; tuberin; Male; Rats; TSC; Animals; Status Epilepticus; haploinsuficience; mužské pohlaví; Everolimus; mTOR; Developmental status epilepticus